Home automation system using X-10 modules for 240V mains power communications - Asmat, Halizan (2001)
This thesis describes the design and development of an intelligent home system using X-10 modules for 240V mains power communications. This system replaces "dumb" electrical outlet and switches found throughout the home with "intelligent" modules controlled by a central computer or central controller. The prototype system consists of a central controller as a transmitter, power line interface (PLI) circuit and a lamp module and appliance module as a receiver. A networking of existing power lines connects these modules and they are assigned with house code and unit code. The controller to identify the modules and to send commands to perform multiple actions by the modules uses these codes. The PLI is used as cost effective ways of coupling X-10 signals/codes onto the AC power line. The specifications and criteria of the system are developed against the available product that is realized in 110V. The system has been tested individually to check its functionality. Only transmitter and receiver gave reliable results while PLI gave erroneous results. Possible causes for the errors are discussed and a study about the power quality in Malaysia need to be done before implementing this system.